Employer Branding and Talent Attraction: Analysis of Its Influence on Generation Z Job Interest - Winarsih Winarsih; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintardjo (Maneggio, 2026)
The global competition for young talent has intensified considerably, and Generation Z born between 1997 and 2012 now constitutes the largest cohort entering the workforce. This study analyzes the influence of employer branding and talent attraction strategies on Generation Z's job interest through a systematic literature review of twenty international peer-reviewed articles published between 2021 and 2023. Findings reveal that Generation Z possesses distinctive work preferences: they prioritize work-life balance, clear career development pathways, organizational culture authenticity, and sustainability values in their employer selection decisions. Effective employer branding for Generation Z must operate through digitally relevant platforms particularly social media such as Instagram, TikTok, and LinkedIn with authentic, interactive, and value-driven content. A clear Employee Value Proposition (EVP) and positive corporate reputation are found to significantly enhance job pursuit intention. This study proposes a three-stage talent attraction model Digital Touchpoints, Employer Brand Perception, and Job Pursuit Intention as a conceptual framework integrating findings from the literature. Managerial implications emphasize the strategic necessity of authentic digital content investment, employee advocacy programs, and alignment of EVP with the core values of Generation Z.